2016
DOI: 10.1002/ppul.23442
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen weaning after hospital discharge in children with bronchopulmonary dysplasia

Abstract: Summary Background In the United States, approximately 12,000 preterm infants are diagnosed with bronchopulmonary dysplasia (BPD) and many of these infants require supplemental oxygen after initial hospital discharge. In children with BPD we sought to identify factors associated with supplemental oxygen use after initial hospital discharge, factors associated with duration of supplemental oxygen use, and methods used to wean off supplemental oxygen in the home environment. Methods All subjects (n = 420) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 13 publications
2
47
0
Order By: Relevance
“…Fourth, minimizing the risk of prolonged oxygen therapy, by minimizing the risk score, should also result in a reduced duration of postoperative oxygen therapy. If oxygen therapy is absolutely necessary, for example when given as a prophylaxis in high risk children or when a respiratory event occurs during anesthesia, weaning children off oxygen therapy should be considered in those who have a low (≤ 7) or intermediate (8–11) risk score as soon as possible when signs and symptoms of hypoxia have improved in order to minimize the consequences of excessive use of postoperative oxygen therapy [ 28 , 29 ]. It has been suggested that an audit of the criteria used for prescribing oxygen such as target saturations, oxygen device used, and indication for use, would help wean children off postoperative oxygen therapy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, minimizing the risk of prolonged oxygen therapy, by minimizing the risk score, should also result in a reduced duration of postoperative oxygen therapy. If oxygen therapy is absolutely necessary, for example when given as a prophylaxis in high risk children or when a respiratory event occurs during anesthesia, weaning children off oxygen therapy should be considered in those who have a low (≤ 7) or intermediate (8–11) risk score as soon as possible when signs and symptoms of hypoxia have improved in order to minimize the consequences of excessive use of postoperative oxygen therapy [ 28 , 29 ]. It has been suggested that an audit of the criteria used for prescribing oxygen such as target saturations, oxygen device used, and indication for use, would help wean children off postoperative oxygen therapy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study from the John Hopkins Hospital, USA 2008–2013, of 154 cases of preterm infants diagnosed with BPD and treated with HOT reported the median age of weaning off oxygen was 12.5 months (95% CI: 10.9–14.2). Children with a continued need for oxygen >12 months of age were more likely to be older at discharge (mean age 3.8 months ±1.3 (0.1–0.72) vs. 5.9 months ±3.7 (2.0–24.5), P < 0.001) and have a gastrostomy tube (13.9% vs. 52.4%, P < 0.001) …”
Section: Pulmonary Sequelaementioning
confidence: 99%
“…Clinicians often assume these pneumonias result from the aspiration of refluxed gastric contents and frequently treat these children with antireflux surgery, fundoplication [3, 4]. Despite this common surgical practice [5, 6], there are no pediatric studies which conclusively show improved pulmonary outcomes after fundoplication, suggesting that the respiratory symptoms seen in aspirating patients may not be related to aspiration of gastric contents [7, 8, 9, 10, 11]. An alternative hypothesis is that aspiration-related respiratory symptoms may result from aspirated oropharyngeal contents.…”
Section: Introductionmentioning
confidence: 99%